(untitled) (Journal of Computational Mathematics, 1994)
In this paper we discuss Specht's plate bending element, give the relationships between ∫_F_ρ wds or ∫_F_ρ ∂w∂n ds and the nodal parameters (or freedoms of degrees), further light on the construction methods for that element and at last introduce a new plate bending element with good convergent properties.